Home advantage and player nationality in international club football - Poulter, D. R. (Journal of Sports Sciences, 2009)
The home advantage effect was investigated at a team and player level in Union of European Football Associations (UEFA) Champions League football using in-depth performance and disciplinary variables. Performance analysis revealed that the home team scored more goals, had more shots on and off target, had a greater share of possession, and won more corners than the away team. There was an opposite trend for disciplinary variables, with the home team committing less fouls than the away team, and receiving less yellow and red cards. There were home advantage effects at player level for goals, total shots, shots on target, assists, and yellow cards, as found in the team analysis. In addition, foreign players demonstrated a home advantage effect for goals scored, whereas domestic players scored an equivalent number of goals at home and away venues. Results are discussed in relation to the home advantage literature and wider implications for the sport.